2003
DOI: 10.1002/bit.10853
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase, but not binding protein, overexpression enhances secretion of a non‐disulfide‐bonded protein in yeast

Abstract: In eukaryotes, secretory proteins are folded and assembled in the endoplasmic reticulum (ER). Many heterologous proteins are retained in the ER due to suboptimal folding conditions. We previously reported that heterologous secretion of Pyrococcus furiosus beta-glucosidase in Saccharomyces cerevisiae resulted in the accumulation of a large fraction of inactive beta-glucosidase in the ER. In this work, we determine the effect of introducing additional genes of ER-resident yeast proteins, Kar2p (binding protein [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…The endoplasmic reticulum has often been recognized as a bottleneck for foreign-protein secretion in yeast (31,32). Manipulation of levels of ER chaperones and foldases improves secretion levels for many yeast foreign proteins, including scFv (9,28,31,33), but overexpression of ER chaperones and foldases does not always help foreign-protein secretion (30,33). Similarly, BiP and PDI did not significantly affect the secretion of fusion proteins in this study, and large amounts of protein were retained intracellularly in a terminal bottleneck.…”
Section: Discussionmentioning
confidence: 50%
“…The endoplasmic reticulum has often been recognized as a bottleneck for foreign-protein secretion in yeast (31,32). Manipulation of levels of ER chaperones and foldases improves secretion levels for many yeast foreign proteins, including scFv (9,28,31,33), but overexpression of ER chaperones and foldases does not always help foreign-protein secretion (30,33). Similarly, BiP and PDI did not significantly affect the secretion of fusion proteins in this study, and large amounts of protein were retained intracellularly in a terminal bottleneck.…”
Section: Discussionmentioning
confidence: 50%
“…Data were restricted to combined overexpression of SIL1, LHS1, and JEM1 in the strain DYB7. Many studies in this field have shown that the beneficial effects of chaperone overexpression are highly substrate dependent (13,43). In this case all three proteins, with distinct characteristics (Table 5), showed increased production levels from shake-flask culture.…”
Section: Discussionmentioning
confidence: 82%
“…While such a strategy increases heterologous protein production in yeast (Shusta et al, 1998;Smith et al, 2004) and insect cells (Ailor and Betenbaugh, 1998;Hsu and Betenbaugh, 1997), it has not consistently achieved the same effects in mammalian cells (Borth et al, 2005;Davis et al, 2000;Kitchin and Flickinger, 1995). Surprisingly, the reduction of the level of endogenous BiP, rather than its overexpression, was found to improve secretion of tissue plasminogen activator in CHO cells (Dorner et al, 1988).…”
Section: Introductionmentioning
confidence: 89%